Are self‐reported risk‐taking behavior and helmet use associated with injury causes among skiers and snowboarders?. Issue 1 (14th November 2013) - Ruedl, G.; Burtscher, M.; Wolf, M.; Ledochowski, L.; Bauer, R.; Benedetto, K.‐P.; Kopp, M.
<x xml:space="preserve">Abstract</x> Over the last 10 years, ski helmet use has steadily increased worldwide. According to the "risk compensation theory, " however, studies found that up to one third of skiers and snowboarders self‐reported to engage in more risk taking when wearing a ski helmet. Therefore, to evaluate whether self‐reported risk taking and ski helmet use affect accident causes on ski slopes, more than 2000 injured skiers and snowboarders were interviewed during the 2011/2012 winter season about accident causes and potential intrinsic and extrinsic risk factors. Chi‐square tests revealed that ski helmet use did not significantly differ between self‐reported risky and cautious people (81% vs 83%). Multivariate regression analysis revealed younger age groups [odds ratios (ORs) 1.8–1.9, P < 005], male sex (OR 2.4, P < 0.001), Austrian nationality (2.2, P < 0.001), higher skill level (1.7, P < 0.001), and off‐slope skiing (OR 2.2, P = 0.060) to be predictive for a risky behavior on ski slopes. Neither the use of skis or snowboards nor accident causes were significantly associated with a riskier behavior on ski slopes. In conclusion, self‐reported risk‐taking behavior and ski helmet use seem not to be associated with accident causes leading to an injury among recreational skiers and snowboarders.